2020
DOI: 10.3389/fpls.2020.570817
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping and Transcriptome Analysis of Virescent Leaf Gene v-2 in Cucumber (Cucumis sativus L.)

Abstract: Leaf color mutants are the ideal materials to explore the pathways of chlorophyll metabolism, chloroplast development and photosynthesis system. In this study, a new virescent leaf mutant 104Y was identified by spontaneous mutation, whose cotyledon and upper five true leaves were yellow color. The yellow true leaves gradually turned green from top to bottom with increased chlorophyll contents. Genetic analysis indicated that the virescent leaf was controlled by one single recessive gene v-2, which was accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Our results revealed that the leaves of the YX-yl mutant exhibited much lower chlorophyll content, especially Chl b content, compared with the wild type, which played an important role in harvesting light and energy conversion. We hypothesized that the yellow phenotype of YX-yl leaves is caused by a deficiency in chlorophyll content, especially Chl b content, which has also been reported in cabbage [ 2 ], wheat [ 7 ], rice [ 6 ], cucumber [ 13 ], foxtail millet [ 8 ], and Arabidopsis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results revealed that the leaves of the YX-yl mutant exhibited much lower chlorophyll content, especially Chl b content, compared with the wild type, which played an important role in harvesting light and energy conversion. We hypothesized that the yellow phenotype of YX-yl leaves is caused by a deficiency in chlorophyll content, especially Chl b content, which has also been reported in cabbage [ 2 ], wheat [ 7 ], rice [ 6 ], cucumber [ 13 ], foxtail millet [ 8 ], and Arabidopsis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The photosynthetic rate and chloroplast ultrastructure are directly affected by leaf color mutations [ 4 , 8 , 13 , 14 , 41 ]. In a leaf-color mutant of rice, the chloroplasts are degrade, the matrix is disordered, and the thylakoids almost completely disappear [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression data of cucumber GATA genes between the first true leaves of green and virescent plant were obtained from our previous study (PRJNA612596) [59]. The expression data of cucumber GATA genes in different tissue (PRJNA80169) [60] and different biotic stresses including downy mildew resistance (PRJNA285071) [61], powdery mildew resistance (PRJNA321023) [62], root-knot nematode resistance (PRJNA419665) [63] were all obtained from Cucurbit Genomics Database (CuGenDB) (http://cucurbitgenomics.…”
Section: Expression Profiles Analysis Of Cucumber Gata Genes With Cucumber Transcriptome Sequencing Big Datamentioning
confidence: 99%
“…Cucumber has many leaf color mutants, including chlorophyll deficient (cd) , light-sensitive (ls) , pale lethal (pl) , golden leaf (g) , golden cotyledon (gc) , yellow cotyledons-1 (yc-1) , yellow cotyledons-2 (yc-2) , yellow plant (yp) , yellow stem (ys) , light green cotyledons-1 (lg-1) , light green cotyledons-2 (lg-2) , virescent (v) , and variegated virescent ( vvi ; Pierce and Wehner, 1990 ). Others include virescent-1 ( v-1 ; Miao et al, 2016 ), virescent-yellow leaf ( vyl ; Song et al, 2018 ), variegated leaf ( vl ; Cao et al, 2018 ), yellow-green leaf ( yg1 ; Ding et al, 2019 ), virescent-2 ( v-2 ; Zhang et al, 2020 ), yellow young leaf-1 ( yyl-1 ; Hu et al, 2020 ), yellow leaf 2.1 ( yl2.1 ; Xiong et al, 2020 ), and albino ( Yan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the spontaneous mutant yg1 with yellow-green leaves is probably caused by mutations in the tandem 13-lipoxygnease (LOX) genes ( Ding et al, 2019 ). The virescent leaf spontaneous mutant v-2 could possibly be caused by a mutation in Csa3G890020 , which encodes the auxin F-box protein ( Zhang et al, 2020 ). An EMS mutagenesis in the CsHD that contains the HD (histidine and aspartate) structural domain proteins synthesizes the yellow leaf mutant, yyl-1 .…”
Section: Introductionmentioning
confidence: 99%